2015
DOI: 10.1016/j.cellsig.2015.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Participation of proteasome-ubiquitin protein degradation in autophagy and the activation of AMP-activated protein kinase

Abstract: Although activation of the AMP-activated protein kinase (AMPK) as well as of ubiquitin/proteasome degradative pathways play an essential role in the preservation of metabolic homeostasis, little is known concerning interactions between protein turnover and AMPK activity. In the present studies, we found that inhibition of the 26S proteasome resulted in rapid activation of AMPK in macrophages, epithelial and endothelial cells. This was associated with increased levels of non-degraded Ub-protein conjugates, in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…It has been reported that AMPK has three major upstream kinases: LKB1, CaMKKb, and TAK1, each of which is activated by different stimuli and in various tissues resulting in diverse outcomes [1,7]. Furthermore, the possibility of crosstalk between AMPK and UPS adds another layer of complexity to the system [29][30][31][32][33]. Considering the importance of AMPK and UPS signaling as two major anticancer strategies, it is important to understand their crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AMPK has three major upstream kinases: LKB1, CaMKKb, and TAK1, each of which is activated by different stimuli and in various tissues resulting in diverse outcomes [1,7]. Furthermore, the possibility of crosstalk between AMPK and UPS adds another layer of complexity to the system [29][30][31][32][33]. Considering the importance of AMPK and UPS signaling as two major anticancer strategies, it is important to understand their crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured mammalian cells, UPS inhibition has been reported to activate AMPK, possibly through relieving proteasomal degradation of AMPK subunits (Jiang et al, 2015; Zungu et al, 2011). Two likely possibilities exist to explain why this phenomenon is not orthologous between cells in culture and C. elegans , 1) that cells in culture are not representative of in vivo signaling and physiology and/or 2) that UPS inhibition of AMPK in C. elegans involves a multi-tissue signaling relay.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal macrophages were isolated, as previously described [32]. Macrophages were elicited in 10-12-wk-old mice by i.p.…”
Section: Peritoneal Macrophages Neutrophils and Monocytes Isolationmentioning
confidence: 99%